2013
DOI: 10.5137/1019-5149.jtn.7750-12.0
|View full text |Cite
|
Sign up to set email alerts
|

Using an autologous fibrin sealant in the preventing of cerebrospinal fluid leak with large skull base defect following endoscopic endonasal transsphenoidal surgery

Abstract: AIm: Postoperative cerebrospinal fluid (CSF) leak following endoscopic endonasal transsphenoidal surgery (EETS) is associated with increased morbidity and mortality. This prospective study is the first evaluation of using autologous fibrin sealant for preventing postoperative CSF leak and related complications. mAterIAl and methOds: 200 endoscopic endonasal transsphenoidal approaches were included in the study and reviewed retrospectively from September 2010 to June 2012. A total of 55 patients who have large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…It is also useful for various types of pathologies such as congenital lesions, hematomas evacuation, tumor excisions, and infective pathologies. [11][12][13] Endoscopic techniques for TN were found to be safe in our study; other authors made similar observations. The endoscopic procedure was very effective with good outcome rate in our study, as other authors have also observed.…”
Section: Discussionsupporting
confidence: 86%
“…It is also useful for various types of pathologies such as congenital lesions, hematomas evacuation, tumor excisions, and infective pathologies. [11][12][13] Endoscopic techniques for TN were found to be safe in our study; other authors made similar observations. The endoscopic procedure was very effective with good outcome rate in our study, as other authors have also observed.…”
Section: Discussionsupporting
confidence: 86%
“…It is a relatively common (up to 30% in posterior fossa surgeries) but potentially avoidable complication (3,10,22). Therefore, preventing CSF leak with watertight closure of dura mater is critical step of neurosurgical operations (15,24,25). Even though there have been several studies exploring various agents and techniques, the quest for the ideal dural sealing technique continues.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the fibrin‐based sealants (Beriplast, Tisseel, Tissucol, Tachosil, and Bolheal) are made from pooled donor human plasma with additional equine collagen (Tachosil), whereas Bioglue contains bovine proteins, incurring the risk exist of transmitting various blood‐borne viruses, prion disease, or allergic reaction to the foreign proteins. These risks are minimized if autologous blood is utilized, such as with Vivostat (Vivostat A/S, Alleroed, Denmark) . Additionally, the use of tissue sealants does increase surgical costs .…”
Section: Intraoperative Considerationsmentioning
confidence: 99%